Digital Communication Studies : A System Literature Review - Nurfaisah, Anggie; Salahudin, Salahudin; Firdaus, Muhammad (Universitas Medan Area, 2024)
The purpose of this writing is to review the literature systematically to show trends related to the study of digital communication. The issue focused on using podcast content for strategic communication. The research uses the literature review method with data sources from the Scopus period 2019-2023 (a total of 195 articles) as well as using VOSviewer to manage the data. The results show the number of Authors on Digital Communication Studies was taken from the last five years of 2019-2023. Then, the largest number of documents on Digital Communication Studies produced by Caplow as many as 2 articles, while the others produced 1 article. By country, the US ranks top with 89 political communications articles in the digital age. Furthermore, research subjects from several journals were used as dominant references discussed (social sciences) 48% but they were interrelated with other topics. Also, the Digital Communication Studies topics cluster is divided into seven clusters that show correlations between the topics that have been studied by researchers. In the last picture showing a visualization of the study density of Digital Communication Studies, the brightest colors indicate topics that are frequently being studied. The limitations of this research come only from Scopus, so further research should use scientific articles taken from well-known international databases such as the Web of Science and Dimensiond Scholar.